2012
DOI: 10.1007/s12160-012-9348-7
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Medicine Approaches to Chronic Obstructive Pulmonary Disease

Abstract: Background Chronic obstructive pulmonary disease (COPD) is a prevalent respiratory disease and associated with considerable individual and socioeconomic burden. Recent research started examining the role of psychosocial factors for course and management of the disease. Purpose This review provides an overview on recent findings on psychosocial factors and behavioral medicine approaches in COPD. Results Research has identified several important psychosocial factors and effective behavioral medicine interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 138 publications
(186 reference statements)
1
29
0
Order By: Relevance
“…Although prevalence estimates for these comorbidities vary greatly due to differences in sampling and the use of different instruments [81], a prevalence of 36% for anxiety and 40% for depression appears to be a valid estimate [82]. The incidence of depression in people with COPD is 2.5 times higher compared with the healthy elderly [83].…”
Section: Promoting Mental Healthmentioning
confidence: 99%
“…Although prevalence estimates for these comorbidities vary greatly due to differences in sampling and the use of different instruments [81], a prevalence of 36% for anxiety and 40% for depression appears to be a valid estimate [82]. The incidence of depression in people with COPD is 2.5 times higher compared with the healthy elderly [83].…”
Section: Promoting Mental Healthmentioning
confidence: 99%
“…Positively attending to and monitoring dyspnoea, and then taking action to manage it, may also increase realistic symptom appraisal and so decrease anxiety about dyspnoea in COPD. Of possible relevance, the results of studies on the use of attentional distraction to reduce perceived exertional dyspnoea in COPD have been mixed, and its use has therefore not been recommended in guidelines (Parshall et al, 2012;von Leupoldt et al, 2012). Carrieri-Kohlman and Murray Gormley (1998) advised against asking COPD patients to distract themselves from acute dyspnoea, after finding that during acute episodes patients reported that they needed to focus on the dyspnoea, with distraction being an ineffective management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…75 Mind-body exercise, such as tai chi and yoga, may be helpful to engage deconditioned patients in physical activity either as a bridge, adjunct, and/or alternative to conventional choices. 77,78 …”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%